breaking boundaries: children activist as epistemic agents within contours of epistemic marginalisation - maldonado castañeda, pedro hernando (childhood & philosophy, 2024)
The article delves into the realm of child environmental activism, portraying it as a concerted response aimed at challenging the prevailing social and political status quo, which systematically underestimates the role of children in decision-making within political and social spheres. It highlights the paramount importance of the epistemological framework that encompasses children’s experiences, emphasising how their exclusion from political and social discourse leads to epistemic marginalisation. This exclusion not only prevents children from assuming the role of epistemic agents but also deprives them of agency and perpetuates existing inequalities. From a philosophical perspective, the article proposes a thorough analysis of children’s epistemic agency, introducing the concept of ’epistemic capability’. It argues that, despite their social marginalisation, knowledgeable children can equip themselves with epistemic resources to interpret their reality and effect change. Furthermore, it posits that environmental activism plays a crucial role as an epistemic resource for children, facilitating the expression of their ideas, challenging dominant narratives, and addressing environmental and social issues head-on. The article emphasises the transformative potential of activism as an epistemic resource, enabling substantive participation and empowering children to navigate and transcend such marginalised circumstances. In conclusion, it highlights how child environmental activism not only challenges the status quo but also provides children with crucial tools for their development as epistemic and social agents, promoting significant change in power dynamics and in the fight for social and environmental justice.